2015
DOI: 10.1124/dmd.114.061705
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance-Associated Protein 3 Plays an Important Role in Protection against Acute Toxicity of Diclofenac

Abstract: Diclofenac (DCF) is a nonsteroidal anti-inflammatory drug commonly prescribed to reduce pain in acute and chronic inflammatory diseases. One of the main DCF metabolites is a reactive diclofenac acyl glucuronide (DCF-AG) that covalently binds to biologic targets and may contribute to adverse drug reactions arising from DCF use. Cellular efflux of DCF-AG is partially mediated by multidrug resistanceassociated proteins (Mrp). The importance of Mrp2 during DCFinduced toxicity has been established, yet the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The sinusoidal efflux of DF-AG into blood, once formed in the liver, is largely dependent on Mrp3 (Lagas et al, 2009). Recently, it was reported that the plasma concentration of DF-AG is 90% lower in Mrp3 gene knockout mice (versus wild-type mice), confirming that basolateral efflux of DF-AG is mediated by Mrp3 (Scialis et al, 2015). These results support the fact that various transporters play an important role in the distribution and elimination of DF-AG.…”
Section: Introductionsupporting
confidence: 73%
“…The sinusoidal efflux of DF-AG into blood, once formed in the liver, is largely dependent on Mrp3 (Lagas et al, 2009). Recently, it was reported that the plasma concentration of DF-AG is 90% lower in Mrp3 gene knockout mice (versus wild-type mice), confirming that basolateral efflux of DF-AG is mediated by Mrp3 (Scialis et al, 2015). These results support the fact that various transporters play an important role in the distribution and elimination of DF-AG.…”
Section: Introductionsupporting
confidence: 73%
“…The argument against covalent adduction as an injury mechanism was supported by our observation that covalent adducts were observed in the liver without apparent toxicity or morphologic changes following DCF administration (Scialis et al, 2015). A possible causal factor for enteropathy is oxidative stress through inhibition of superoxide dismutase (SOD), which is a critical cellular defense mechanism for coping with reactive oxygen species (ROS) (Fridovich, 1978).…”
Section: Introductionmentioning
confidence: 53%
“…We observed that mice lacking the efflux transporter Mrp3 were more susceptible to intestinal injury compared with WT (Scialis et al, 2015). Though the intestinal toxicity differences between WT and KO were unequivocal, the mechanisms behind those differences were uncertain.…”
Section: Mechanisms Of Toxicity Caused By Diclofenac Acyl Glucuronidementioning
confidence: 77%
See 2 more Smart Citations